Structural specialties, curiosities, and record-breaking features of crustacean reproduction - Vogt, Günter (Journal of morphology, 2016)
Crustaceans are a morphologically, physiologically, and ecologically highly diverse animal group and correspondingly diverse are their reproductive characteristics. They have evolved structural specialties with respect to penis construction, sperm form, sperm storage, fertilization, and brood care. Unique in the animal kingdom are safety lines that safeguard hatching and first molting. Further curiosities are dwarf males in parasitic and sessile crustaceans and bacteria-induced feminization and gigantism of crustacean hosts. Record-breaking features are relative penis length, sperm size, clutch size, chromosome number, viability of dormant eggs, and fossil ages of penis, sperm, and brooded embryos. These examples from a single invertebrate subphylum and a single life history aspect illustrate that morphological solutions to functional requirements can be as spectacular as behavioral adaptations. They may provide valuable sources for comparative morphologists, ecologists, evolutionary biologists, and applied biologists to advance topical issues such as sperm competition, posthumous paternity, evolution of brood care, adaptation to freshwater, infectious feminization, sustainable male-based fishery, maintenance of genetic diversity under conditions of limited mating opportunity, and long-term impact of pollution on genotype and phenotype. J. Morphol. 277:1399-1422, 2016. © 2016 Wiley Periodicals, Inc.